Study design and rationale of the pAtients pResenTing with cOngenital heaRt dIseAse Register (ARTORIA‐R). (12th September 2021) - Sinning, Christoph; Zengin, Elvin; Diller, Gerhard‐Paul; Onorati, Francesco; Castel, María‐Angeles; Petit, Thibault; Chen, Yih‐Sharng; Lo Rito, Mauro; Chiarello, Carmelina; Guillemain, Romain; Coniat, Karine Nubret‐Le; Magnussen, Christina; et al.
Abstract: Aim: Due to improved therapy in childhood, many patients with congenital heart disease reach adulthood and are termed adults with congenital heart disease (ACHD). ACHD often develop heart failure (HF) as a consequence of initial palliative surgery or complex anatomy and subsequently require advanced HF therapy. ACHD are usually excluded from trials evaluating heart failure therapies, and in this context, more data about heart failure trajectories in ACHD are needed to guide the management of ACHD suffering from HF. Methods and results: The pAtients pResenTing with cOngenital heaRt dIseAse Register (ARTORIA‐R) will collect data from ACHD evaluated or listed for heart or heart‐combined organ transplantation from 16 countries in Europe and the Asia/Pacific region. We plan retrospective collection of data from 1989–2020 and will include patients prospectively. Additional organizations and hospitals in charge of transplantation of ACHD will be asked in the future to contribute data to the register. The primary outcome is the combined endpoint of delisting due to clinical worsening or death on the waiting list. The secondary outcome is delisting due to clinical improvement while on the waiting list. All‐cause mortality following transplantation will also be assessed. The data will be entered into an electronic database with access to the investigators participating in the register. All variables of the register reflect key components important for listing of the patients or assessing current HF treatment. Conclusion: The ARTORIA‐R will provide robust information on current management and outcomes of adults with congenital heart disease suffering from advanced heart failure.